THE ROLE OF CREATIVITY IN ENTREPRENEURIAL SUCCESS - Ani Kusumaningsih; Silvia Ekasari; Adih Supriadi; Titis Nistia Sari; Akbar Tanjung (CV. Adiba Aisha Amira, 2025)
Creativity is an important element in the entrepreneurial process, forming the foundation for innovative ideas that drive business success. Entrepreneurship is the quality of a person's conscience, character, and will that enables them to creatively bring new ideas into the world. Someone who applies entrepreneurial principles will work independently, by starting their own business and using available resources creatively and innovatively. he approach is a review of the literature using knowledge of earlier studies' data obtained from journals. references on the internet relating to the role of creativity in entrepreneurial success. Based on this study, it was found that success in the world of entrepreneurship really depends on the level of creativity, because creativity functions in driving and developing business. In other words, business progress and success is closely related to the level of innovation that can be produced. A new venture's success can be greatly influenced by its creative energy. Whether it's creating original goods or services or coming up with creative fixes for problems, others' creativity can serve as a catalyst for their own successful entrepreneurship.